Mapeamento e análise da pesquisa acadêmica sobre o fundo de garantia do tempo de serviço (FGTS) no Brasil - Sandro Pereira Silva; Isabella Guimar\~aes Bernardes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This study aimed to map and analyze the scientific production on the Severance Pay Guarantee Fund (FGTS) in Brazil, which is aimed at both social protection and financing housing and urban infrastructure. To this end, we sought to categorize its thematic scope as a strategic public policy instrument and identify patterns of evolution over time in its multiple approaches. We identified 90 academic studies, including master's dissertations and doctoral theses, defended in Brazilian higher education institutions spread across all regions of the country, in programs in different areas of knowledge, which allowed us to demonstrate the multidimensional nature of the FGTS's operation since its creation in 1966.
Keywords: J08; G20; H54; 330; FGTS; public policies; social protection; housing financing; labor rights